Prioritization of zakat distribution in selangor and the Federal Territory of Malaysia: Are they following the right distribution principles according to Shariah? - Hassan, Rusni; Muhammad Nasir, Nur I’ffah (International Islamic University Malaysia, 2016)
This study reviews and analyzes the current practice of zakat distribution in Selangor and the Federal Territory of Malaysia. It is observed that within recent years, zakat distribution in Selangor and the Federal Territory to fi sabilillah recipients constitutes the highest percentage as compared to other groups of recipients. Hence, there is a need to study the relevance of prioritizing fi sabilillah over the other groups of recipients because the more the allocation channeled to a particular group, the more the chances that the rest will eventually have less portion from the zakat. Therefore, the group which is prioritized should have a more significant impact in realizing the goal of zakat. In order to do so, a few aspects must be analysed, including the principle of prioritization or preference in zakat distribution from the Shariah perspective, the definition or interpretation of zakat recipients adopted by these two states and also the zakat allocation method practiced by them. Several recommendations are proposed to improve the zakat distribution in both States.